Detection of Mycobacterium avium subsp. paratuberculosis in Infected Tissues by New Species-Specific Immunohistological Procedures - Coetsier, Christophe (American Society for Microbiology, 1998)
We have previously described the cloning and sequencing of a gene portion coding for the terminal part of a 34-kDa protein of Mycobacterium avium subsp. paratuberculosis, the etiological agent of Johne’s disease (P. Gilot, M. De Kesel, L. Machtelinckx, M. Coene, and C. Cocito, J. Bacteriol. 175:4930–4935, 1993). The recombinant polypeptide (a362) carries species-specific B-cell epitopes which do not cross-react with other mycobacterial pathogens (M. De Kesel, P. Gilot, M.-C. Misonne, M. Coene, and C. Cocito, J. Clin. Microbiol. 31:947–954, 1993). The present work describes the preparation of polyclonal and monoclonal antibodies directed against a362 and the use of these immunoglobulins for histopathological diagnosis of Johne’s disease. The new immunohistological procedures herewith detailed proved to be able to identify M. avium subsp. paratuberculosis antigens in the intestinal tissues and lymph nodes of cattle affected by either the paucibacillary or pluribacillary form of the disease. They yielded negative responses not only with healthy animals but also with those affected by tuberculosis (Mycobacterium bovis). Both immunohistological procedures proved to be as sensitive as or more sensitive than Ziehl-Neelsen staining and, in addition, to be endowed with species specificity.